Urban landscapes as therapeutic landscapes : the transforming conceptions of care environments - Pyykkönen, Siiri; Kymäläinen, Päivi (Geographical Society of Finland, 2025)
Psychiatric hospitals are increasingly being built in urban landscapes, in contrast to many of the old hospitals which were located in peripheral areas close to nature. This indicates a change in the conception of therapeutic landscapes: rural natural landscapes have been replaced by a more relational and fluid understanding and practices where therapeutic environments are created in relation to society, communities, networks and everyday urban life. We examine how the conception of therapeutic landscapes was constituted in the planning process of the urban psychiatric hospital in Turku, Finland, by analyzing the arguments and discourses on therapeutic elements in the planning materials. The findings reveal how the shift from inpatient care towards outpatient care has redirected attention away from hospitals. Instead of relying on healing by natural elements in remote locations, everyday environments, artificial landscapes and multifunctional spaces are now expected to create therapeutic atmospheres.